Monumental restoration in Lima in the period 1920-1990 - Hayakawa Casas, José Carlos (2002)
With a relative banality, many experts and professionals committed with the monumental restoration and conservation in Lima ventured to formulate visions of the historical evolution that had this discipline without considering the specificity of their own process. The realizationof this investigation work, by way of break point, it tries to emphasize rigorously in this specificity and to demonstrate her own development degree and inner dynamics.